How do socially responsible companies engage in tax avoidance practices? Evidence from France - Lakhal, Faten; Ben Saad, Itidel; Lakhal, Nadia; Gaaya, Safa (Management international / International Management / Gestiòn Internacional, 2024)
Corporate social responsibility (CSR) is part of the larger debate on whether firms engage in CSR to promote social interests or strictly to achieve legitimacy and thus are implicitly involved in some form of greenwashing. This paper investigates the effect of CSR on tax avoidance. Based on a sample of French listed companies, the results show that firms engaging in CSR adopt tax avoidance practices. The results also show that the disciplinary roles of debt and corporate governance mitigate this positive effect. Additional evidence shows that family-owned firms overinvesting in CSR are unlikely to engage in tax avoidance for socioeconomic wealth purposes. The results are robust to alternative measures of tax avoidance and endogeneity concerns.